Genome-wide identification of Major Intrinsic Proteins in Glycine soja and characterization of GmTIP2;1 function under salt and water stress - Da-yong Zhang (Nature Portfolio, 2017)
Abstract In different plant species, aquaporins (AQPs) facilitate water movement by regulating root hydraulic conductivity under diverse stress conditions such as salt and water stresses. To improve survival and yield of crop plants, a detailed understanding of stress responses is imperative and required. We used Glycine soja genome as a tool to study AQPs, considering it shows abundant genetic diversity and higher salt environment tolerance features and identified 62 Gs AQP genes. Additionally, this study identifies major aquaporins responsive to salt and drought stresses in soybean and elucidates their mode of action through yeast two-hybrid assay and BiFC. Under stress condition, the expression analysis of AQPs in roots and leaves of two contrasting ecotypes of soybean revealed diverse expression patterns suggesting complex regulation at transcriptional level. Based on expression analysis, we identify GmTIP2;1 as a potential candidate involved in salinity and drought responses. The overexpression of GmTIP2;1 in Saccharomyces cerevisiae as well as in-planta enhanced salt and drought tolerance. We identified that GmTIP2;1 forms homodimers as well as interacts with GmTIP1;7 and GmTIP1;8. This study augments our knowledge of stress responsive pathways and also establishes GmTIP2;1 as a new stress responsive gene in imparting salt stress tolerance in soybean.